2013
DOI: 10.1002/jps.23337
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Modeling of Hepatocyte Growth Factor in Experimental Animals and Humans

Abstract: Running title:Pharmacokinetic model of HGF after single and repeated dosesThe second and third authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…We have previously indicated that the basic pharmacokinetic profiles and parameters obtained from experimental animal species (mouse, rat and monkey) could be extrapolated to those in humans [29]. Our present results indicate that the pharmacokinetic profiles of HGF in patients with kidney diseases may be stable, perhaps regardless of the severity of the kidney injury.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…We have previously indicated that the basic pharmacokinetic profiles and parameters obtained from experimental animal species (mouse, rat and monkey) could be extrapolated to those in humans [29]. Our present results indicate that the pharmacokinetic profiles of HGF in patients with kidney diseases may be stable, perhaps regardless of the severity of the kidney injury.…”
Section: Discussionsupporting
confidence: 54%
“…A previous pharmacokinetic analysis indicated that the plasma HGF levels tend to decrease rapidly and that HGF is primarily accumulated in the liver [13,14]. When HGF was administered intravenously, plasma HGF decreased in 2 distinct phases [29]. The α-phase (the 1st phase) that corresponds to the steep decrease in plasma HGF within 30 min is attributable to an association of HGF with capillary vessels and cell surface binding sites [12,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these findings in animals, HGF has not yet been found effective in the therapeutic treatment of chronic fibrotic diseases in humans 7 . However, HGF is being investigated as a possible treatment for renal failure due to its role as a mitogenic and motogenic factor, which may help stimulate kidney regeneration 70 . Studies in a mouse model of Duchenne muscular dystrophy demonstrated that HGF is being suppressed by NF-κB signaling, and that knock-out of the NF-κB gene, or use of NF-κB chemical inhibitors leads to an increase in HGF transcription and skeletal HGF levels stimulating HGF-induced muscle repair 55 .…”
Section: 2 Therapeutic Implicationsmentioning
confidence: 99%